2021
DOI: 10.3390/jcm10245900
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Injury as a Prognostic Factor in Mid- and Long-Term Follow-Up of COVID-19 Survivors

Abstract: Myocardial injury, which is present in >20% of patients hospitalized for COVID-19, is associated with increased short-term mortality, but little is known about its mid- and long-term consequences. We evaluated the association between myocardial injury with one-year mortality and readmission in 172 COVID-19 patients discharged alive. Patients were grouped according to the presence or absence of myocardial injury (defined by hs-cTn levels) on admission and matched by age and sex. We report mortality and hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
(66 reference statements)
0
10
1
Order By: Relevance
“…To date, only few studies regarding the cardiovascular longterm consequences after recovery fromCOVID-19 have been published (Supplementary Table 1), suggesting worse long-term outcomes (69)(70)(71)(72). In our previous published study of a cohort with 172 patients who survived COVID-19 hospitalization, myocardial injury was associated with poor prognosis, mainly due to a higher number of readmissions (71). In the same direction, Kini et al (70) found that the risk of death at 30 days was significantly increased in those patients who had myocardial injury during the acute phase.…”
Section: Prognostic Implications Of Myocardial Damage In Covid-19 Pat...mentioning
confidence: 99%
“…To date, only few studies regarding the cardiovascular longterm consequences after recovery fromCOVID-19 have been published (Supplementary Table 1), suggesting worse long-term outcomes (69)(70)(71)(72). In our previous published study of a cohort with 172 patients who survived COVID-19 hospitalization, myocardial injury was associated with poor prognosis, mainly due to a higher number of readmissions (71). In the same direction, Kini et al (70) found that the risk of death at 30 days was significantly increased in those patients who had myocardial injury during the acute phase.…”
Section: Prognostic Implications Of Myocardial Damage In Covid-19 Pat...mentioning
confidence: 99%
“…[4][5][6][7][8] In our previous study on this topic, we found an incidence of aPH, based on echocardiographic criteria, of 39% in Covid-19 patients admitted to intensive care (ICU) and that early mortality (21 days) was increased more than 6-fold compared to patients without signs of aPH. 4 In previous follow-up reports on hospitalized Covid-19 patients, 9,10 the issue of aPH has not been reported in any detail.…”
Section: Introductionmentioning
confidence: 99%
“…In previous follow‐up reports on hospitalized Covid‐19 patients, 9,10 the issue of aPH has not been reported in any detail. Against the results of our previous study, we hypothesized that mortality may continue to be elevated after 1 month in patients with Covid‐19 and aPH.…”
Section: Introductionmentioning
confidence: 99%
“…There is little information on the long-term consequences of COVID-19 in patients after hospital discharge. Most studies have been limited to hospitalized individuals, and all had a short duration of follow-up and narrow selection of cardiovascular outcomes (12)(13)(14). Recently, a large study showed that, beyond the first 30 days of infection, people with COVID-19 exhibited increased risk for and 12-month burden of cardiovascular diseases (15).…”
Section: Introductionmentioning
confidence: 99%